Knowledge and attitudes toward mild traumatic brain injury among patients and family members - He, Jian; Chen, Zhongliang; Zhang, Jianjun; Liu, Xiao (Frontiers in Public Health, 2024)
This study aimed to investigate the knowledge and attitudes toward mild traumatic brain injury (mTBI) among patients and their family members. A cross-sectional study was conducted between July 1, 2023 and September 30, 2023 at Zhejiang Hospital among patients and their family members of mTBI. Demographic information, knowledge and attitudes were collected through online questionnaire distribution. A total of 573 valid questionnaires were analyzed, comprising 289 males (50.44%) and 284 females (49.56%). Of the total respondents, 258 individuals (45.03%) had experienced a concussion once. The mean knowledge and attitudes scores were 11.00 ± 2.75 (possible range: 0 - 20) and 27.78 ± 4.07 (possible range: 8 - 40). The findings from the multivariate logistic regression analysis indicate a negative independent association between monthly per capita income ranging from 5,000 to 10,000 RMB and scores related to knowledge and attitudes (β = -0.160, 95% CI: [-3.245-0.210], P = 0.026). Having a middle school education was independently associated with a decreased likelihood of positive attitudes towards mTBI (OR = 0.378, 95% CI: [0.163-0.874], P = 0.023), while suffering mTBI due to falling from a height or similar causes was independently associated with an increased likelihood of positive attitudes (OR = 3.588, 95% CI: [1.274-10.111], P = 0.016). These findings underscore the need for healthcare professionals to prioritize education for patients and their families. Ensuring that comprehensive information regarding the causes, symptoms, and consequences of mTBI is accessible will likely enhance knowledge and foster more positive attitudes.